2023
DOI: 10.34172/ijhpm.2023.7089
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Implementing Interventions for Reducing Avoidable Hospital Readmission: Systematic Review of Qualitative Studies

Abstract: Background: Avoidable hospital readmission is a major problem among health systems. Although there are effective peri-discharge interventions for reducing avoidable hospital readmission, successful implementation is challenging. This systematic review of qualitative studies aimed to identify barriers and facilitators to implementing peri-discharge interventions from providers’ and service users’ perspectives. Methods: We searched four databases for potentially eligible qualitative studies from databases’ incep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…According to a recently published SR, implementing interventions for reducing hospital readmissions usually faces a number of common challenges across different health system contexts (Fu et al, 2023). These common challenges include limited resources, incompatibility between new interventions with existing work routines, poor communication among team members, complex implementation processes, and insufficient understanding of the content and effectiveness of the new interventions (Fu et al, 2023). These challenges are well documented in case studies originating from health systems in developed countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a recently published SR, implementing interventions for reducing hospital readmissions usually faces a number of common challenges across different health system contexts (Fu et al, 2023). These common challenges include limited resources, incompatibility between new interventions with existing work routines, poor communication among team members, complex implementation processes, and insufficient understanding of the content and effectiveness of the new interventions (Fu et al, 2023). These challenges are well documented in case studies originating from health systems in developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…In Hong Kong, nongovernmental organizations (NGO) provide a large portion of community care and support for older people, either independently or with funding from the Government's Social Welfare Department (2021) (Lau et al, 2018). As fragmentation of the health and social care system could result in poor patient outcomes, how to enhance medico-social collaboration has also been discussed (Chan According to a recently published SR, implementing interventions for reducing hospital readmissions usually faces a number of common challenges across different health system contexts (Fu et al, 2023). These common challenges include limited resources, incompatibility between new interventions with existing work routines, poor communication among team members, complex implementation processes, and insufficient understanding of the content and effectiveness of the new interventions (Fu et al, 2023).…”
Section: Implications For Policy and Practicementioning
confidence: 99%
See 1 more Smart Citation
“…While extractions from qualitative studies were coded directly against the CFIR constructs, quantitative data was first narratively synthesised and then analysed together with the extractions from qualitative studies. The number of included studies describing a particular CFIR construct was reported, yielding a reporting frequency (RF) 39 . Barriers and facilitators described in three or more included studies were considered ‘commonly reported’.…”
Section: Methodsmentioning
confidence: 99%
“…The number of included studies describing a particular CFIR construct was reported, yielding a reporting frequency (RF). 39 Barriers and facilitators described in three or more included studies were considered 'commonly reported'. Lastly, given the context dependency of barriers and facilitators, especially within complex health and social systems, 36 inductive analysis focused on identifying emerging themes among these commonly reported barriers and facilitators.…”
Section: Data Synthesismentioning
confidence: 99%